External Validation and Recalculation of the CODEX Index in COPD Patients. A 3CIAplus Cohort Study. (2nd January 2019) - Almagro, Pere; Martínez-Camblor, Pablo; Miravitlles, Marc; Rodríguez-Carballeira, Mónica; Navarro, Annie; Lamprecht, Bernd; Ramirez-Garcia Luna, Ana S; Kaiser, Bernhard; Alfageme, Inmaculada; Casanova, Ciro; Esteban, Cristobal; Soler-Cataluña, Juan J; et al.
Abstract: The CODEX index was developed and validated in patients hospitalized for COPD exacerbation to predict the risk of death and readmission within one year after discharge. Our study aimed to validate the CODEX index in a large external population of COPD patients with variable durations of follow-up. Additionally, we aimed to recalculate the thresholds of the CODEX index using the cutoffs of variables previously suggested in the 3CIA study (mCODEX). Individual data on 2, 755 patients included in the COPD Cohorts Collaborative International Assessment Plus (3CIA+) were explored. A further two cohorts (ESMI AND EGARPOC-2) were added. To validate the CODEX index, the relationship between mortality and the CODEX index was assessed using cumulative/dynamic ROC curves at different follow-up periods, ranging from 3 months up to 10 years. Calibration was performed using univariate and multivariate Cox proportional hazard models and Hosmer-Lemeshow test. A total of 3, 321 (87.8% males) patients were included with a mean ± SD age of 66.9 ± 10.5 years, and a median follow-up of 1, 064 days (IQR 25–75% 426–1643), totaling 11, 190 person-years. The CODEX index was statistically associated with mortality in the short- (≤3 months), medium- (≤1 year) and long-term (10 years), with an area under the curve of 0.72, 0.70 and 0.76, respectively. The mCODEX index performed better in the medium-term (<1 year) than the original CODEX, and similarly in the long-term. In conclusion, CODEX and mCODEX index are good predictors of mortality in patients with COPD, regardless of disease severity or duration of follow-up.